Performance Enhancement of Decode and Forward Relaying Network in a Log- normal Fading Channel using Diversity Technique - I, Ojo Samson; O, Abolade Robert; L, Alagbe Oluwaseun; A, Ojerinde Idowu; O, Tooki Oluwaseun (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
The demand for wireless communication services is increasing daily due to several emerging applications of wireless communication system. However, the services provided by wireless communication is affected by obstruction along the path of propagation resulting in scattering of signal at the receiver. Decode and Forward (DF) relaying network used in addressing the problem also suffer from signal outage at the destination due to inability of relay to decode the transmitted signal at the relay node. Hence, in this paper, performance enhancement of DF relaying network is proposed using Time Diversity (TD) at the source with hybrid Threshold Combiner and Equal Gain Combiner (TC-EGC) at the destination. The various copies of the transmitted signal are received at the DF relay node to carry out relay selection by selecting relay with signal strength greater than the set threshold of 3 dB. The selected relays decode and re-encode the received signal before been propagated to the destination. The various copies of the signal received at the destination with varying paths ‘L’ (2, 3 and 4) are combined using TC-EGC. Mathematical expressions of Outage Probability (OP) and Bit Error Rate (BER) for the proposed technique are derived using Probability Density Function (PDF) of the signal received. The proposed DF technique is simulated using MATLAB R2018a and validated using OP and BER by comparing with the conventional DF cooperative relaying network. The proposed technique improved the performance of conventional DF cooperative relaying network with reduced BER and OP.